Engineering for Steel Construction - Disque, Robert O. (Engineering Journal, 1984)
Structural engineers are increasingly aware of the importance of details and connections in steel structures. These are not only the key to economy but also may be the source of trouble. For this reason, AISC has just released a new 370-pg. textbook— Engineering for Steel Construction —for the advanced detailer and design engineer. The new book is a companion to Detailing for Steel Construction, which was written for the beginning detailer who might have a high school education. Since both books are self-contained, some material may be common to both. Together, the books, which replace the 2nd Edition of Structural Steel Detailing, are geared to the 8th Edition Manual of Steel Construction.